An Application on Prisoners Treatment Model Based of Islamic Religion in The Correctional Institusions - Irma Cahyaningtyas; Nina Mirantie Wirasaputri (Ijtimā`iyya: Journal of Muslim Society Research, 2020)
Guidance for prisoners is carried out in Correctional Institution. This must be in line with the objectives of treatment so that what is emphasized in the treatment process is a model of fostering prisoners. The problems in this article are first, what the form of treatment model for prisoners in Correctional Institutionat this time is; and second, how the development of Islamic-based treatment models is applied to prisoners at Correctional Institution. This article uses empirical legal research with socio legal approach. The specifications in this article are descriptive analytical research specifications and studies conducted in Corrections Institutions. The results of the discussion in this article show that the model of treament for prisoners carried out in the Correctional Institution is currently based on the principle of correctional guidance. namely individual treatment and classical treatment. Renewal of the development of a model of treatment for prisoners can be done religiously, which prioritizes a religious approach that aims to create soft skills, namely treatment the of repentance and the character of trust in prisoners themselves.